Find d/dx tan⁻¹ a+bx/b-ax
Answers
Answered by
0
we have to find the value of ![\frac{d}{dx}tan^{-1}\frac{a+bx}{b-ax} \frac{d}{dx}tan^{-1}\frac{a+bx}{b-ax}](https://tex.z-dn.net/?f=%5Cfrac%7Bd%7D%7Bdx%7Dtan%5E%7B-1%7D%5Cfrac%7Ba%2Bbx%7D%7Bb-ax%7D)
d/dx [tan^-1{(a + bx)/(b - ax)}] = 1/[1 + (a + bx)²/(b - ax)²] × d{(a + bx)/(b - ax)}/dx
= (b - ax)²/[(b - ax)² + (a + bx)²] × [(b - ax) × b - (a + bx) × (-a)]/(b - ax)²
= (b - ax)²/[b² + a²x² + a² + b²x²] × [{b² + a²}/(b - ax)²}]
= (b - ax)²/[(x² + 1)(a² + b²)] × [(b² + a²)/(b - ax)²]
= (b - ax)²/(x² + 1) × 1/(b - ax)²
= 1/(1 + x²)
hence answer is 1/(1 + x²)
d/dx [tan^-1{(a + bx)/(b - ax)}] = 1/[1 + (a + bx)²/(b - ax)²] × d{(a + bx)/(b - ax)}/dx
= (b - ax)²/[(b - ax)² + (a + bx)²] × [(b - ax) × b - (a + bx) × (-a)]/(b - ax)²
= (b - ax)²/[b² + a²x² + a² + b²x²] × [{b² + a²}/(b - ax)²}]
= (b - ax)²/[(x² + 1)(a² + b²)] × [(b² + a²)/(b - ax)²]
= (b - ax)²/(x² + 1) × 1/(b - ax)²
= 1/(1 + x²)
hence answer is 1/(1 + x²)
Similar questions